Pembelajaran Produk Kreatif Dan Kewirausahaan Melalui Pemanfaatan Business Center di SMK PGRI Kota Tegal - Amelia, Indah -; Hendaryati, Neni; Faridah, Faridah (Universitas Negeri Makassar, 2021)
This study aims to explore and find out in depth the learning of creative products and entrepreneurship in class XII students through the use of the business center at SMK PGRI Tegal City. The sources of information in this study were teachers of creative products and entrepreneurship, business center administrators, and 3 students of class XII of the Marketing Expertise Program. Data collection techniques with observation, interviews and documentation. The data were analyzed using a case study descriptive analysis technique with the stages of data collection, data analysis, data reduction, data presentation and conclusion drawing. The results of this study indicate that learning creative products and entrepreneurship has taken advantage of the business center. Through the use of the business center, the entrepreneurial spirit of students grows to enter the business world. Based on the results of this study, it is recommended that 1) For teachers, it is expected to be able to take full advantage of the school's business center facilities, 2) For School Leaders, school leaders are expected to evaluate the implementation of learning that occurs in schools, supervise the use of school facilities